2012
DOI: 10.3198/jpr2011.08.0407crc
|View full text |Cite
|
Sign up to set email alerts
|

Registration of ‘Barduro’ Mid‐Dormant Red Clover

Abstract: ‘Barduro’ (Reg. No. CV‐31, PI 664479) red clover (Trifolium pratense L.) is a synthetic cultivar selected for mid‐dormancy and high resistance to root‐knot nematodes (RKN; Meloidogyne spp.). Pest resistance and plant dormancy are critical factors for adaptation of red clover into the southeastern United States. The objective of this program was to select for a mid‐dormancy response between transitional‐zone cultivars and the nondormant ‘Southern Belle’, while maintaining RKN resistance. A population of 3250 pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Marked variability in this photoperiod response has been observed among red clover cultivars and is believed to be quantitatively inherited (Quesenberry and Blount, 2012). The University of Florida forage breeding program has released less‐dormant cultivars (‘Cherokee’ [Quesenberry et al, 1993] and ‘Southern Belle’ [Quesenberry et al, 2005]), with earlier initiation of spring growth, and an intermediate‐early cultivar ‘Barduro’ (Quesenberry and Blount, 2012). However, even Southern Belle is markedly later in production than crimson clover, and it has been suggested that an even earlier producing red clover would be desirable.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Marked variability in this photoperiod response has been observed among red clover cultivars and is believed to be quantitatively inherited (Quesenberry and Blount, 2012). The University of Florida forage breeding program has released less‐dormant cultivars (‘Cherokee’ [Quesenberry et al, 1993] and ‘Southern Belle’ [Quesenberry et al, 2005]), with earlier initiation of spring growth, and an intermediate‐early cultivar ‘Barduro’ (Quesenberry and Blount, 2012). However, even Southern Belle is markedly later in production than crimson clover, and it has been suggested that an even earlier producing red clover would be desirable.…”
mentioning
confidence: 99%
“…Conversely, release from dormancy and initiation of spring growth is suggested to be a response to lengthening days and increases in soil temperatures in spring (Kendall and Stringer, 1985). Marked variability in this photoperiod response has been observed among red clover cultivars and is believed to be quantitatively inherited (Quesenberry and Blount, 2012). The University of Florida forage breeding program has released less‐dormant cultivars (‘Cherokee’ [Quesenberry et al, 1993] and ‘Southern Belle’ [Quesenberry et al, 2005]), with earlier initiation of spring growth, and an intermediate‐early cultivar ‘Barduro’ (Quesenberry and Blount, 2012).…”
mentioning
confidence: 99%
“…Figure1illustrates the range of dormancy among these cultivars compared to Kenton, a cultivar bred in Kentucky USA. Our two most recent releases, FL24D(Quesenberry et al, 2015b) and Barduro(Quesenberry & Blount, 2012) are respectively, markedly earlier, and somewhat later than Southern Belle. Early spring is a time of critical forage deficit in Florida, and Figure2illustrates the marked differences in forage availability between the most southern and more…”
mentioning
confidence: 67%
“…Forage germplasm collection records document that these transition zones yield materials with unique dormancy and hardiness characteristics. These zones have daily rate of change in day length in late winter to early spring, and similarly in late fall and early winter, that has enabled breeders to readily select for small differences in dormancy response (Deren & Quesenberry, 1989; Kenworthy et al, 2017; Quesenberry & Blount, 2012; Williams et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Both can also be used in conjunction with seeking US Plant Variety Protection, although only a few public red clover cultivars have sought Plant Variety Protection. Since 2008, the following red clover cultivars have been registered in the Journal of Plant Registrations : ‘AU Red Ace’ (Mosjidis, 2011), ‘Barduro’ (Quesenberry and Blount, 2012), ‘FL24D’ (Quesenberry et al, 2015), and Freedom!MR (Taylor, 2008). Since 2008, the following red clover cultivars have gone through the AOSCA variety review board: ‘Bearcat’ (2016), FF 9615 (2013, 2015), ‘FSG 401RC’ (2012, 2014), ‘FSG 402’ (2013), ‘Gallant’ (2012, 2013), ‘Resilience’ (2017), ‘Rustler’ (2012), and ‘SS‐0303RCG’ (2012, 2014).…”
mentioning
confidence: 99%